Analisis Capaian Kapitasi Berbasis Kinerja Fasilitas Kesehatan Tingkat Pertama di Wilayah Jakarta Timur pada Masa Pandemi Covid-19 - Ryan Augustian; Dumilah Ayuningtyas (Syntax Corporation, 2023)
Universal Health Coverage is a global commitment in the context of equitable health development. In Indonesia, implementation has been strengthened by the social insurance mechanism through the JKN program since 2014. Health services at the primary level provided by FKTPs are key, but the performance of JKN services in FKTPs as measured by performance-based capitation (KBK) has so far not been achieved and varies widely, as well as in East Jakarta. The COVID-19 pandemic, which has lasted more than 2 years, has increasingly burdened FKTP. It is important to know the achievements of KBK in East Jakarta during the pandemic and related factors in order to formulate recommendations for improvement for FKTP and related parties so that JKN participants get higher quality services. Mixed method with sequential explanatory design is done to get a more in-depth explanation qualitatively from the results of quantitative research. Quantitative data analysis was carried out with multivariate binary logistic regression, while qualitative data analysis was the result of in-depth interviews with coding, categorization and thematization. Result: KBK achievements during the pandemic period were not achieved, especially the Contact Number Indicator and RPPT. Puskesmas have a greater chance than primary clinics in achieving KBK after the number of participants, the number of human resources, the ratio of doctors to participants, accreditation status, and the availability of an integrated P-Care information system are controlled. (OR= 5 ). The service process, provision of service and managerial support, existing resources and regulations can explain the difference between a puskesmas and a pratama clinic.